Algal biomass and diesel emulsions: An alternative approach for utilizing the energy content of microalgal biomass in diesel engines. (15th June 2016) - Xu, Yanan; Hellier, Paul; Purton, Saul; Baganz, Frank; Ladommatos, Nicos
Graphical abstract: Highlights: Diesel engine tests of algal slurry diesel emulsions with up to 6.6% wt/wt biomass. Novel surfactant package developed for preparation of stable emulsions. Engine work increased with algal biomass concentration and emulsion energy content. Algal slurry emulsions emitted lower exhaust NOx and PM than fossil diesel. Intact algae cells were found after high pressure fuel injection but not in exhaust PM. Abstract: The use of algal biomass for the production of sustainable biofuels has attracted significant interest due to the fast reproduction rates and high lipid content of many microalgal species. However, existing methods of extracting algal cellular lipids are complex and expensive, with regards to both energy input and economic costs. This work explores an alternative method of utilizing the energy content of microalgae through the preparation of wet algal biomass slurry/fossil diesel emulsions containing up to 6.6% wt/wt algae biomass, using a specific surfactant combination, for direct injection diesel engine combustion of microalgae without prior biomass drying or lipid extraction. A high lipid containing green microalgae, Chlorella sorokiniana, was used to produce algal biomass for the study. The preparation of wet algal slurry/diesel emulsions from algae grown under standard conditions, and also those under conditions intended to increase cellular lipid content or growth rates was investigated, and in all cases a surfactant pack of Span80, CTAB and butanol was found to produce a stable emulsion. A correlation between the engine work produced during combustion of the emulsions in a modern direct injection compression ignition and the lower heating value of the wet slurry emulsions was found, with no evidence of individual algae cells persisting to the engine exhaust. Engine exhaust emissions of nitrogen oxides (NOx) and particulate matter were lower for all of the wet algal slurry/diesel emulsions relative to a reference fossil diesel tested under similar conditions, while in the case of the emulsion prepared from algal biomass to which a flocculating agent had been added, emissions of carbon monoxide (CO) were found to increase significantly.